Remediating Strategic Intervention Material (RSIM) for Statistics and Probability - Tambong, Christian F.; Malonisio, Manuel O. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This multiphase mixed methods design research was conducted to develop a Remediating Strategic Intervention Material (RSIM) for Statistics and Probability for Grade 10 students. Research findings revealed that problem solving as the most essential skill in any area of learning is not given too much attention and importance as shown by the least learned competencies in Statistics and Probability of the majority of Aklanon students. In fact, 4 out of 4 or 100% of their least learned competencies involve problem solving activities. These competencies are: (1) Solves problems involving permutations and combination, (2) Solves problems involving probability, (3) Calculates specified measure of position (e.g., 90th percentile) of a set of data and (4) Finds the probability of (A U B). Hence, the researcher developed a Remediating Strategic Intervention Material (RSIM) in response to these competencies with the integration of different learning activities in line with the suggested teaching strategies of the teachers. The developed material was then evaluated by the students and teachers using the Pilot Testing Tool and Learning Resource (LR) Quality Assurance Tools. After the evaluation, the material was found acceptable in terms of its content, language and layout and format. Moreover, students and teachers expressed their satisfaction with the material highlighting its suitability, simplicity, relatability and comprehensiveness These results underscore the potential of targeted intervention materials in strengthening problem solving competencies, a challenge common in mathematics education worldwide. This study offers valuable insights to curriculum developers and educators to bridge foundational skills through localized and innovative intervention materials.